PENINGKATAN MOTIVASI DAN HASIL BELAJAR BAHASA INGGRIS TENTANG PEMAHAMAN ISI BACAAN TEKS RECOUNT MELALUI METODE NHT PESERTA DIDIK KELAS VIII B SMP NEGERI 3 ADIWERNA - NUR ZUMROTI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
This study aims to increase motivation and learning outcomes in the English subject for class VIII B Recount text at SMP Negeri 3 Adiwerna in the 2021/2022 academic year, using the NHT method. The type of research used was Classroom Action Research (CAR) which was carried out in two cycles to see the learning process and the improvement of student learning outcomes in participating in learning Recount text material through the NHT method. The subjects of this research were class VIII B students of SMP Negeri 3 Adiwerna, totaling 32 students. Data collection techniques in PTK consist of tests and non-tests. Data collected on each test and non-test activity from the implementation of each PTK cycle were analyzed descriptively using the percentage technique to see the learning process and the improvement of learning outcomes. The results of the study can be concluded with the learning model "NHT method" motivation and learning outcomes in English for Recount text materials increase. The results of the study motivation questionnaire increased from the initial condition of 56.25% to 78,12% in cycle 1 (there was an increase of 21,87%) and increased to 87,50 % in cycle 2 (an increase of 12,51%). While the learning outcomes of Recount text material in the initial conditions were 53.12%, increased to 65.63% in cycle 1 (there was an increased 12,51%), and increased again to 87.50% in cycle 2 (there was an increased 21,87%). Based on the results of the study it was concluded that the application of the "NHT method" learning model could improve motivation and learning outcomes in English for class VIII B Recount text at SMP Negeri 3 Adiwerna for the 2021/2022 academic year. ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar mapel Bahasa Inggris materi teks Recount kelas VIII B SMP Negeri 3 Adiwerna Tahun Pelajaran 2021/2022, dengan penerapan metode NHT. Jenis penelitian yang dipakai adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan pada dua siklus untuk melihat proses belajar dan peningkatan hasil belajar peserta didik dalam mengikuti pembelajaran materi teks Recount melalui metode NHT. Subyek penelitian ini adalah peserta didik kelas VIII B SMP Negeri 3 Adiwerna, berjumlah 32 peserta didik. Tehnik pengumpulan data dalam PTK ini terdiri dari tes dan non tes. Data yang dikumpulkan pada setiap kegiatan tes dan non tes dari pelaksanaan setiap siklus PTK dianalisis secara deskriptif dengan menggunakan tehnik presentase untuk melihat proses belajar dan peningkatan hasil belajar. Hasil penelitian dapat disimpulkan dengan model pembelajaran “metode NHT” motivasi dan hasil belajar Bahasa Inggris materi teks Recount meningkat. Hasil kuesioner motivasi belajar mengalami peningkatan dari kondisi awal 56,25% menjadi 78,12% pada siklus 1 (ada kenaikan 21,87%) dan meningkat menjadi 90,63% pada siklus 2 (meningkat 12,51%). Sedangkan hasil belajar materi teks Recount pada kondisi awal 53,12%, meningkat menjadi 65,63% pada siklus 1 (ada peningkatan 12,51%), dan meningkat lagi 87,50% pada siklus 2 (ada peningkatan 21,87%). Berdasarkan hasil penelitian diperoleh kesimpulan bahwa penerapan model pembelajaran “metode NHT” dapat meningkatkan motivasi dan hasil belajar Bahasa Inggris materi teks Recount kelas VIII B SMP Negeri 3 Adiwerna tahun pelajaran 2021/2022.